Pengaruh Trichokompos TKKS dan Pupuk N, P, K terhadap Pertumbuhan dan Hasil Tanaman Okra (Abelmoschus esculentus L.) - Wibowo, Galih Yuswa; Ariani, Erlida; Idwar, Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Okra is a vegetable plant have long been cultivated in Indonesia, has many benefits, but have not been a lot of consumption. Okra can grow well on sandy soils with high organic matter.This research aims to examine the effect of interactions as well as the main factors of TrichocompostTKKS and N, P, K fertilizersand get a dose of trichocompost interactions of N, P, K fertilizers better against the growth of crops and okra. This research was conducted at the experimental garden ofthe Faculty of Agriculture, University of Riau in January-April 2018 in the form of experiments multiplied with 3x4 arranged according to RAL. The first factor of the Trichocompost (T), namely: T0 = without trichocompost, T1 = 5 ton.ha-1and T2 = 10 ton.ha-1. The second factor of N, P, K fertilizer: N0= without fertilizer N, P, K, N1 = (35 kg N, 18 kg P2O5, 30 kg K2O).ha-1, N2 = (46 kg N, 27 kg P2O5, 45 kg K2O).ha-1,N3= (57,5 kg N, 36 kg P2O5, 60 kg K2O).ha-1.The results showed that the interaction Trichocompost TKKS and fertilizers N, P, K has significant effect on flowering age and the dry weight of the plant. The trichocompostTKKS has significant effect on the number of leaves, against the weight of the fruit per plant, the dry weight of the plant, while N, P, K fertilizer gave significant effect on plant height, flowering age, weightfruit per plant, weight dried plants. Trichocompost 5 tons.ha-1 and N, P, K(35 kg N, 18 kg P2O5, 30 kg K2O).ha-1can give you the best results against the growth of crops and okra.Â Keywords: Okra, Trichocompost, Urea, SP-36, KCl fertilizer